"This is an illness. No one is supposed to be treated badly": community-based stigma assessments in South Africa to inform tuberculosis stigma intervention design - Isabel Foster; Amanda Biewer; Nosivuyile Vanqa; Goodman Makanda; Phumeza Tisile; Sally E. Hayward; Dillon T. Wademan; Michaile G. Anthony; Rachel Mbuyamba; Michelle Galloway; Wieda Human; Helene-Mari van der Westhuizen; et al. (BMC, 2024)
Abstract Background Though tuberculosis (TB)-related stigma is a recognized barrier to care, interventions are lacking, and gaps remain in understanding the drivers and experiences of TB-related stigma. We undertook community-based mixed methods stigma assessments to inform stigma intervention design. Methods We adapted the Stop TB Partnership stigma assessment tool and trained three peer research associates (PRAs; two TB survivors, one community health worker) to conduct surveys with people with TB (PWTB, n = 93) and caregivers of children with TB (n = 24) at peri-urban and rural clinic sites in Khayelitsha, Western Cape, and Hammanskraal, Gauteng Province, South Africa. We descriptively analyzed responses for each stigma experience (anticipated, internal, and enacted), calculated stigma scores, and undertook generalized linear regression analysis. We conducted 25 in-depth interviews with PWTB (n = 21) and caregivers of children with TB (n = 4). Using inductive thematic analysis, we performed open coding to identify emergent themes, and selective coding to identify relevant quotes. Themes were organized using the Constraints, Actions, Risks, and Desires (CARD) framework. Results Surveys revealed almost all PWTB (89/93, 96%) experienced some form of anticipated, internal, and/or enacted stigma, which affected engagement throughout the care cascade. Participants in the rural setting (compared to peri-urban) reported higher anticipated, internal, and enacted stigma (β-coefficient 0.72, 0.71, 0.74). Interview participants described how stigma experiences, including HIV intersectional stigma, act individually and together as key constraints to impede care, leading to decisions not to disclose a TB diagnosis, isolation, and exclusion. Stigma resilience arose through the understanding that TB can affect anyone and should not diminish self-worth. Risks of stigma, driven by fears related to disease severity and infectiousness, led to care disengagement and impaired psychological well-being. Participants desired counselling, identifying a specific role for TB survivors as peer counselors, and community education. Conclusions Stigma is highly prevalent and negatively impacts TB care and the well-being of PWTB, warranting its assessment as a primary outcome rather than an intermediary contributor to poor outcomes. Multi-component, multi-level stigma interventions are needed, including counseling for PWTB and education for health workers and communities. Such interventions must incorporate contextual differences based on gender or setting, and use survivor-guided messaging to foster stigma resilience.